Topography and Morphology of a Hydrogel Enriched with Allantoin for Biomedical Purposes - Saucedo Acuña, Rosa Alicia (2018)
The intention to obtain a biodegradable hydrogel enriched with allantoin is to conform a medium of distribution for this natural extract. In this case allantoin was distributed in two layers. This article shows the topography and morphology of this interesting biomaterial by SEM and confocal microscopy